Role of Harmaline in Inhibiting c-Myc, Altering Molecular Typing, and Promoting Apoptosis in Triple-Negative Breast Cancer - Xu H; Ma Y; Li H; Song X; Liu Y; Mierzhakenmu Z; Yan K; Xu R; Zhao Z; Yuan H; Dong C (Breast Cancer: Targets and Therapy)
Haoyi Xu,1 Yan Ma,2 Huiling Li,1 Xinyu Song,1 Yuanjing Liu,1 Zuliyaer Mierzhakenmu,1 Kang Yan,1 Rui Xu,1 Ziqian Zhao,1 Hongyi Yuan,1 Chao Dong1 1Department of Breast and Thyroid Surgery, the Third Clinical Medical College of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830000, People’s Republic of China; 2Department of Gynecological Surgery, the Third Clinical Medical College of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830000, People’s Republic of ChinaCorrespondence: Chao Dong, Department of Breast and Thyroid Surgery, the Third Clinical Medical College of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830000, People’s Republic of China, Tel +86 139 9911 1211, Email dc_dongchao@outlook.comObjective: Triple-negative breast cancer (TNBC) lacks effective targeted, endocrine therapeutic agents and the development of novel agents is costly and time-consuming. The objective of this study was to identify pharmaceuticals and natural products utilized in clinical practice that have the potential to inhibit the expression of Cellular-myelocytomatosis oncogene (c-Myc), based on a review of the current literature. The aim was to assess the effect of the specified drugs on c-Myc expression in TNBC cells, determine the most potent inhibitor, and evaluate its impact on TNBC cell proliferation, invasive migration, and apoptosis, as well as the expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER-2) at both the gene and protein levels. Explore its potential for treatment or adjuvant therapy for triple-negative breast cancer.Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot were used to quantify gene and protein expression levels. Flow cytometry was employed to measure cell proliferation and apoptosis, while the Transwell assay was utilized to assess cell invasion and migration.Results: Harmaline emerged as the strongest inhibitor, significantly decreasing the expression of c-Myc at both the gene and protein levels in TNBC cells. It also inhibited cell proliferation, invasion, and migration while promoting apoptosis in TNBC cells. Additionally, there was a varying increase in the expression of ER and PR genes and proteins. While the expression of the HER-2 gene was elevated, there was no significant change in HER-2 protein levels. Notably, the expression of the phosphorylated HER-2 protein increased.Conclusion: Harmaline was found to promote apoptosis and inhibit cell proliferation, invasion, and migration in TNBC cells by targeting the inhibition of c-Myc. It also induced the re-expression of the ER, PR, and HER-2 genes, as well as the ER and PR proteins.Keywords: c-Myc, harmaline, molecular typing, triple-negative breast cancer